RUANG PUBLIK DAN PEREMPUAN DI KOREA SELATAN - Sonezza Ladyanna (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
This article discusses the public space in South Korea relating to women's rights. The purpose of this article is to investigate the existence of friendly public spaces for women. The researcher wants to know how to improve and equip the facilities in order to make friendly public spaces for women. This research found that the public spaces on campus and public toilets have sufficient rights of women so that women can feel comfortable. The conducive of public spaces supported by legal professionals can control a person's social behavior in addition to an effective moral education.